INFLUENCE OF SOCIO-ECONOMIC VARIABLES ON ORGANIC FOOD PURCHASE INTENTION AMONG HEALTHCARE WORKERS IN SOUTH-EAST NIGERIA (Journal of the Management Sciences, 2025)
This study investigates the influence of socio-economic variables on organic food purchase intention among healthcare workers in South-East Nigeria. Organic food consumption has gained global attention due to increasing awareness of its health, environmental, and ethical benefits. However, in developing countries like Nigeria, socio-economic factors may pose significant barriers to its adoption, even among informed populations such as healthcare professionals. Using a quantitative research design, data were collected through an online questionnaire targeting healthcare workers across the region. Key socio-demographic variables analysed include income level, educational attainment, occupational status, and marital status. Findings revealed that all these variables significantly influenced the intention to purchase organic food. Higher income, advanced education, and professional status were positively associated with stronger purchase intentions, while marital status showed moderate influence. The combined model of socio-economic variables significantly predicted organic food purchase intention. The study recommends policy incentives, awareness campaigns, and institutional support to promote organic food consumption among health professionals and the broader public. It also highlights the importance of leveraging healthcare workers as health-conscious role models in sustainable consumption advocacy.
Keywords: Organic food; purchase intention; socio-economic variables; healthcare workers, income; education